Development of an Integrated Transaction and Payroll Information System Using the Waterfall Model: A Case Study in Small Enterprise - Cindy Atika Rizky; Mardiah Mardiah (Journal of Information Technology and Systems Engineering, 2026)
Transaction and payroll data processing in small enterprises is often conducted manually, leading to disorganized records, processing delays, and difficulties in retrieving accurate information. These challenges highlight the need for an integrated information system to improve data management efficiency and effectiveness. This study aims to develop an integrated transaction and payroll information system using the Waterfall model in a small enterprise as a case study. The research adopts a descriptive approach, with data collected through observation, interviews, and literature review, while the system development follows a sequential approach comprising analysis, design, implementation, testing, and maintenance. The system is designed using a structured analysis approach, including Data Flow Diagram (DFD) and Entity-Relationship Diagram (ERD) modeling, and implemented in Borland Delphi with a MySQL database. The results indicate that the developed system significantly improves data processing speed, simplifies transaction and payroll management, and produces more accurate and integrated reports. System testing demonstrates that the application is user-friendly, visually appealing, and capable of supporting efficient data processing. Therefore, the proposed information system enhances operational efficiency and information quality, with practical implications for small enterprises in supporting data-driven decision-making.